2015
DOI: 10.1007/s00228-015-1934-8
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective handling of perhexiline: implications regarding accumulation within the human myocardium

Abstract: Metabolism PharmacokineticsDrug uptake Stereoselectivity 3 ABSTRACT (150-250 words)Purpose: Perhexiline is a prophylactic anti-ischaemic agent with weak calcium antagonist effect which has been increasingly utilized in the management of refractory angina. The metabolic clearance of perhexiline is modulated by CYP2D6 metaboliser status and stereoselectivity. The current study sought to determine (1) whether the acute accumulation of perhexiline in the myocardium is stereoselective, and (2) to investigate the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 29 publications
(38 reference statements)
1
14
0
Order By: Relevance
“…Similar tissue accumulation has previously been reported for (±)‐perhexiline in animals and humans . Indeed, in this study, both total and individual enantiomer concentrations in plasma and heart following administration of the racemate to rats were similar to those observed clinically . Although there was no evidence of substantial enantioselectivity in the in vivo uptake of perhexiline into human myocardium following clinical administration of racemate, this current study has revealed significant enantioselectivity in the hepatic and myocardial distribution of (+)‐ and (−)‐perhexiline, but it was evident only following administration of the pure enantiomers.…”
Section: Discussionsupporting
confidence: 89%
“…Similar tissue accumulation has previously been reported for (±)‐perhexiline in animals and humans . Indeed, in this study, both total and individual enantiomer concentrations in plasma and heart following administration of the racemate to rats were similar to those observed clinically . Although there was no evidence of substantial enantioselectivity in the in vivo uptake of perhexiline into human myocardium following clinical administration of racemate, this current study has revealed significant enantioselectivity in the hepatic and myocardial distribution of (+)‐ and (−)‐perhexiline, but it was evident only following administration of the pure enantiomers.…”
Section: Discussionsupporting
confidence: 89%
“…Chemical shifts (δH) are given in parts per million (ppm) as referenced to the appropriate residual solvent peak. 13 C NMR spectra: these were recorded at 101 MHz on a Bruker ADVANCE III 400 instrument. Chemical shifts (δC) are given in parts per million (ppm) as referenced to CHCl3.…”
Section: Methodsmentioning
confidence: 99%
“…1) of perhexiline have suggested differences in myocardial uptake, clearance, route of metabolism and, potentially, activity and toxicity; however, it is not yet clear as to whether these data will translate to therapeutic relevance. 13,14,15 Perhexiline has been described as a drug of "low potency, low specificity, and low selectivity" and as having actions on a diverse range of molecular targets, some of which remain to be properly defined, which contribute to its therapeutic benefit in heart failure (HF). 16 However, at present, the therapeutic action of perhexiline is generally still thought to be due to inhibition of CPT-1 and to a lesser extent CPT-2.…”
Section: Introductionmentioning
confidence: 99%
“…and 3 In a more recent follow6up, the conclusion of Chong and colleagues that PHX does exhibit saturability is not supported by their data (see 103 , Fig 2A and B). Given these observations, it is difficult to conceive of how long6term PHX administration, even with maintenance of plasma concentrations of the drug at around 1 QM, would not lead to the steady accumulation of toxic levels of PHX.…”
Section: + and ' ! !mentioning
confidence: 82%
“…As discussed above then under therapeutic dosing regimens (i.e. at its limit of solubility of 0.06 mg / L), effectively all of the drug would exist in the cationic form (≈ 99.9%, 0.05994 mg / L) with the neutral form present at just 0.00006 mg / L. If the tiny amount of the neutral form of the drug (≈ 60 ng / L in the plasma) was the only species able to transfer across the cell surface membrane, myocardial concentrations of the drug at 6 -10 mg /kg103, 112 would establish an intracellular:plasma concentration gradient of 100,000:1. It is inconceivable that such massive accumulation could be supported by simple passive transfer of the neutral form of the drug from the plasma into cells, even if one considers that the neutral species that does partition across the surface membrane would be immediately protonated (to its cationic form) in the cellular environment (Figure 2).…”
mentioning
confidence: 99%